Pemanfaatan RFID (Radio Frequency Identification) Tag Sebagai Alternatif Efektifitas Pemantauan Kehadiran Warga Sekolah di SMK Swagaya 2 Purwokerto Berbasis Website dengan Menggunakan Metode Uji Kualitas Mccall’s Quality - Candrasari, Diwahana Mutiara; Prihatmajaya, Putu Samuel; Fransiska, Clara Adelia; Pernada, Elisabeth (Joined Journal (Journal of Informatics Education); Vol 5 No 2 (2022): Volume 5 Nomor 2 (2022)DO - 10.31331/joined.v5i2.2296, 2022)
Along with technological developments that are growing very rapidly, all people or agencies need changes in their work processes to follow technological developments, one of which is, population data processing is an important activity that is carried out continuously by the SMK Swagaya 2 Purwokerto. When the current system often encounters difficulties in the attendance process, finding duplicate data for absences because they forget that they have been absent and then absent again, waste paper used. The purpose of this study was to build an attendance system at SMK Swagaya 2 Purwokerto. The Attendance Information System uses RFID where the user uses a tag card that can detect data about the person. Techniques in collecting data using direct or indirect observation methods and interview methods. The development of an information system is expected to help SMK Swagaya 2 Purwokertoin processing data for Principals, Employees or Teachers, Students during attendance, reducing paper waste and paper waste and can shorten operating time. With the existence of storage media in the form of a good database, it is expected to increase the efficiency of the Swagaya 2 Purwokerto Vocational School with the presence of an attendance information system, which is faster and the application used can provide convenience for users.